IMPROVING THE AUDIT OF FINANCIAL LIABILITIES BY DEVELOPING THE RELATIONSHIP BETWEEN THE MATERIALITY AND THE AUDIT PROCEDURES - Nicolai RUSSU (Economica, 2023)
The most important aspects of the research are based on the overall study of legal relationships, accounting methodologies and the spectrum of perspective views of the financial audit of financial liabilities presented by the author. The research is focused on the methodological delimitation of the materiality applicable in financial accounting and the one applicable in financial audit for the correct assessment of sources and their use for specific purposes, as well as their influence on the audit results. At the same time, the audit procedures were identified and selected based on materiality research and establishing the complementary relationship. The study also focuses on the application of professional judgment to build a reasoned structure through which the audit procedures present a solid foundation of the materiality applicable in the audit, delimited from that used in financial accounting, as well as identifying the influence and impact of these actions on the information in the audit report.